Enhancing the electrical conductivity of carbon black-filled immiscible polymer blends by tuning the morphology - Pan, Yamin; Liu, Xian Hu; Hao, Xiaoqiong; Stary, Zdenek; Schubert, Dirk W. (European Polymer Journal, 2016)
Blends of carbon black (CB)-filled polystyrene (PS) and poly(methyl methacrylate) (PMMA) with different PS/PMMA ratios have been prepared by melt blending in order to obtain conductive polymer composites with a low electrical percolation threshold according to the concept of double percolation. The dependence of the electrical conductivity on the morphology of the composite was examined before and after annealing in the molten state. The electrical conductivity of the composites was highest when the PS and PMMA phases formed a co-continuous structure and CB particles were selectively located and percolated in the PS phase. PS/PMMA (30/70) blends exhibited the lowest electrical percolation threshold of 1.26 vol% CB. A simple model is suggested to explain this effect. After annealing, the CB clearly affected the stabilization of the co-continuous structure. Moreover, the electrical conductivity increased after annealing and the percolation threshold decreased to below 1 vol% CB regardless of PS content. The largest increase in electrical conductivity after annealing was found with PS/PMMA (70/30) blends filled with 1 vol% CB. With increasing PMMA content, this effect became less pronounced. The different behaviors in the composites can be explained by dynamic percolation and decrease in continuity of the CB-filled PS phase induced by structure coarsening.
Keywords: Annealing; Electrical properties; Interface; Phase morphology; Polymer composites